ENSEMBLE MUSIC AS EDUCATIONAL AND COMMUNICATIVE RESOURCE. ONLINE SEMINAR REVIEW - Valentina L. Boiko; Svetlana A. Mitasova; Sergey G. Chaikin (Russian Studies in Culture and Society, 2024)
Music has always been a magnet for the greatest minds of mankind considering it as a cultural phenomenon, as manifestation of Divinity, and as a specific art form. Philosophic studies of music nature show that origins of spiritual culture can be seen as deep as in the earliest civilization periods.